Assessment of the volunteer movement in the public consciousness of the Dagestan population - Rashid Omarievich Ramazanov (Вестник Майкопского государственного технологического университета)
In the post-soviet period, the existing volunteerism was replaced by volunteering, which has different forms of expression (cultural, social, political, environmental, etc.). The issue of determining the demand for volunteering and volunteer movement in the modern Russian society has become relevant for a number of reasons, including changes in the social well-being of the population, the inefficiency of the social policy of the state, the emergence of socially unprotected strata that require the attention and help of caring and active citizens. The purpose of the research is to identify the assessment and attitude towards the volunteer movement that exists in the public consciousness of the Dagestan population.The research method is a mass standardized survey. The study shows there is a positive attitude towards socially useful work on a voluntary basis with motivation in the mass consciousness of the Dagestanis, that, firstly, it helps to educate the principles of mercy, moral qualities, collectivism in society, and secondly. In society there is the need to carry out socially useful work on a voluntary basis (helping the sick, the elderly and lonely people, environmental problems, participation in sports events, etc.). The results of the survey indicate that the surveyed Dagestan population is aware of volunteer activities, but at the same time, the respondents demonstrate passive behavior with a weakly expressed civic activity. However, empiricism shows that a certain part of the young generation of the Dagestanis is ready to take an active part in the volunteer movement, to provide the necessary social and other assistance to the categories of the population that need it.